2016
DOI: 10.5455/ajvs.222088
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of Listeria Monocytogenes Isolated from Different Sources

Abstract: The aim of this study was to determine the differences concerning phenotypic and genotypic characters of L.monocytogenes isolated from different sources (100 meat, 100 offals, 100 fish and 100 ready to eat foods-RTE-which is represented by luncheon) on the basis of pathogenicity and antibiotic resistance. To achieve this aim, bacteriological examination was done according to ISO 11290 amendment 2004.then confirmed by biochemical reactions and serotyping, then antimicrobial susceptibility testing which indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Furthermore, Kamar et al [19], in Egypt, detected hlyA gene in all L. monocytogenes isolated from different sources. Moreover, Lotfollahi et al [20], in Iran, found the prevalence of hlyA is 100% from dairy and meat products.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Kamar et al [19], in Egypt, detected hlyA gene in all L. monocytogenes isolated from different sources. Moreover, Lotfollahi et al [20], in Iran, found the prevalence of hlyA is 100% from dairy and meat products.…”
Section: Discussionmentioning
confidence: 99%